ANALISIS DETERMINAN RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN PENYAKIT JANTUNG ISKEMIK DI RUMAH SAKIT TINGKAT II DUSTIRA KOTA CIMAHI JAWA BARAT - Ahmad, Nasir; Sihombing, Rosmariana (Institut Kesehatan Immanuel, 2019)
In West Java, the prevalence of Coronary Heart Disease according to age 15 years is above the national prevalence of 1.6%. The number of cases of ischemic heart disease in Dustira Level II Hospital tends to increase from year to year. This shows that heart disease is a serious disease and needs attention in its prevention efforts. The purpose of this study is to know the most dominant risk determinant that is associated with the incidence of ischemic heart disease in Dustira Level II Hospital in 2017. The type of research used is quantitative with a case control study design. The sample size in the study was 83 cases and 83 controls (1:1). Case: People diagnosed with ischemic heart disease based on the patient's medical record in 2017 at Dustira Hospital. Control: People who have never been diagnosed with ischemic heart disease are based on the patient's medical record in 2017 at Dustira Hospital. Data analysis using bivariate analysis with Chi-square test (: 0.05 and CI: 95%), and multivariate analysis with logistic regression approach. The results of the bivariate analysis of variables related to the incidence of ischemic heart disease were people who did not work (OR= 2 and = 0.047) and people who had a history of hypertension (OR= 3.29 and = 0,000). Variables that are not related to the incidence of ischemic heart disease are Age> 45 years (OR= 1.49 and = 0.276), gender (OR= 1.60 and = 0.157) and area of residence (OR = 1.25 and = 0.532). The most dominant multivariate variable causing ischemic heart disease was history of hypertension (Exp (B) = 3,215). Keywords: Heart Ischemic Disease, Risk Determinants, Dustira Hospital